Detection of Amyloid-β(1–42) Aggregation With a Nanostructured Electrochemical Sandwich Immunoassay Biosensor - Wang, Bing-Yu; Gu, Bien-Chen; Wang, Gou-Jen; Yang, Yuan-Han; Wu, Chia-Che (Frontiers in Bioengineering and Biotechnology, 2022)
Amyloid-β(1–42) [Aβ(1–42)] oligomer accumulations are associated with physiologic alterations in the brains of individuals with Alzheimer’s disease. In this study, we demonstrate that a nanostructured gold electrode with deposited gold nanoparticles, induced via electrochemical impedance spectroscopy (EIS), may be used as an Aβ(1–42) conformation biosensor for the detection of Alzheimer’s disease. Monoclonal antibodies (12F4) were immobilized on self-assembled monolayers of the electrochemical sandwich immunoassay biosensor to capture Aβ(1–42) monomers and oligomers. Western blot and fluorescence microscopy analyses were performed to confirm the presence of Aβ(1–42) monomers and oligomers. EIS analysis with an equivalent circuit model was used to determine the concentrations of different Aβ(1–42) conformations in this study. We identified conformations of Aβ(1–42) monomers and Aβ(1–42) oligomers using probe antibodies (12F4) by employing EIS. RAβ(1−42) indicates the sum resistance of impedance measured during Aβ(1–42) immobilization. ΔR12F4 refers to the concentration of probe antibody (12F4) binding with Aβ(1–42). The concentration of Aβ(1–42) oligomer was defined as the percentage of Aβ(1–42) aggregation R12F4/RAβ(1−42). The experimental results show that the biosensor has high selectivity to differentiate Aβ(1–40) and Aβ(1–42) monomers and Aβ(1–42) oligomers and that it can detect Aβ(1–42) oligomer accurately. The linear detection range for Aβ(1–42) oligomers was between 10 pg/ml and 100 ng/ml. The limit of detection was estimated to be 113 fg/ml.